Cinema art deco: o moderno necessário - Luz, Maria de Lourdes de Oliveira (1993)
The work consists in a reading of Art Deco viewed through the Carioca Cinemas of the third and fourth decades of this century. For this purpose we have chosen a representative group of buildings to serve as instrument. Art Deco as tied into the Cinema was considered a neutral space and inevitable in the transition from the reigning ecleticism of the nineteenth century to aseptic modernism. In order to understand why necessary modernism was evoked, a critical review has been made of the true Art Deco of the 1925 Exposition of Decorative and Industrial Arts in Paris and its antecedents which made possible conceptual and formal changes. An analysis has been made of theoretical bases which permeated the movement adding to the magic of the Cinema and its influence on everyday life.The Cinema Metro serves as model.